The Advantages and Disadvantages of ICT in Teaching Foreign Languages - Erkinova Sevinch Jamshidovna (International Journal on Integrated Education, 2022)
The utilization of ICT in Foreign language Educating and Learning is vital for giving open doors for educators and learners to learn and work in a data age. Training, especially foreign language instruction needs to adjust and reestablish itself to be viable in the globalized society. This study plans to examine the utilization of ICT in foreign language educating and realizing, which are the advantages, the primary benefits of ICT, and the difficulties of ICT in a foreign language. The acknowledgment, what’s more, execution of ICT in educating is a mix of difficulties for our general public. One of the needs of the Training in Uzbekistan is the coordination of ICT in training, so the utilization of ICT in language educating and learning appears to have become essential to the modernization of the school system and learning techniques. Utilizing credible material given by the web assists learners with being better in correspondence and to be in touch with the way of life of the nation and individuals whose language they study.